The C.O.O.K.I.E acronym strategy: a mnemonic approach to English verb learning - Marisol Márquez Martínez; Atti Herawati; Octa Pratama Putra (Universitas Sarjanawiyata Tamansiswa, 2026)
This study investigates the implementation of the C.O.O.K.I.E acronym strategy—a food-based mnemonic approach—to facilitate young learners’ acquisition of English verb forms in a joyful and meaningful manner. The research aims to explore how these mnemonic associations can mitigate the abstraction of grammar rules and enhance both cognitive retention and affective engagement. Employing a qualitative descriptive case study, the research involved five purposively selected fourth-grade elementary students in Jakarta. The intervention consisted of three intensive learning sessions where students were introduced to various mnemonic acronyms, such as B.U.R.G.E.R, P.I.Z.Z.A, into I.C.E C.R.E.A.M. Data were triangulated through participatory observation, structured student reflections, and performance-based tasks focusing on verb conjugation. The qualitative data were analyzed using the Miles and Huberman framework, involving data reduction, data display, and thematic verification. The findings reveal that the strategy significantly improved the students' ability to recall and practice English verbs. Beyond cognitive enhancement, the food-related mnemonics fostered high emotional engagement, with students describing the process as ‘fun’ and ‘relatable’. The results suggest that linking linguistic structures to familiar semantic categories (food) reduces learning anxiety and transforms rote memorization into a more intuitive process. This study concludes that the acronym-based strategy promotes ‘brain-friendly’ learning by integrating logical memorization (left brain) with imaginative visualization (right brain). This approach offers a potent pedagogical alternative for elementary EFL classrooms, advocating for a shift from mechanical drills to enjoyable, imaginative grammar instruction.